ACLS for EMTs - Smith, Mike (EMS continuing education series, 2013)
EMTs can find themselves in critical situations that require advanced cardiac life support (ACLS). Although EMTs are not trained to provide advanced-level skills, there is much they can do to improve the quality of management, and thus the patient?s chance for survival by understanding ACLS and facilitating its administration by ALS providers. Teamwork is the cornerstone of ACLS care. Advanced life support can only function on a foundation of solid, ongoing basic life support practices. As such, an understanding of the principles of advanced life support will enhance the ability of EMTs to work in collaboration to increase the survival rates of patients. Most importantly, better teamwork will improve care not only during cardiac arrests, but also during all emergency calls. ACLS for EMTs familiarizes the reader with cardiac emergencies, the skills used to manage them, and teamwork principles that ensure the best possible patient outcomes.